Konsep Adoption dan Sanctification di dalam Doktrin Keselamatan - Israel I. Adu; Vrichilya E. Lessy; Sofia Mangke; James Palk (EUANGGELION: Jurnal Teologi dan Pendidikan Kristen, 2024)
Abstract: Since humans fell into sin, Jesus Christ has been the person who acts as the Reconciler between humans and God. Sin has separated humans and God, but with the work of the cross of Christ, He has adopted humans to be His children and sanctified them so that they can be saved from the penalty of death. Man is saved by God through Jesus Christ. Those who believe in Him have been adopted as His children and sanctified so that they can grow in Him, and ultimately so that they can become like Christ. So, the truth about the concept of Adoption and Sanctification is a fundamental concept that needs to be firmly understood because it is directly related to saving faith. The firm concept of Adoption and Sanctification is able to ward off polemics or doubts about the status of believers before God. This research uses qualitative methods by describing the concepts of Adoption and Sanctification through scientific studies of systematic theology.Abstrak: Sejak manusia jatuh ke dalam dosa, Yesus Kristus merupakan pribadi yang berperan sebagai Pendamai antara manusia dengan Allah. Dosa telah memisahkan manusia dan Allah, namun dengan karya salib Kristus, Ia telah mengangkat manusia menjadi anak-anak-Nya dan menguduskan mereka sehingga mereka dapat diselamatkan dari hukuman maut. Manusia diselamatkan oleh Allah melalui Yesus Kristus. Mereka yang percaya kepada-Nya telah diangkat menjadi anak-Nya dan disucikan supaya bertumbuh di dalam Dia, dan akhirnya supaya dapat menjadi serupa dengan Kristus. Kebenaran tentang konsep Adoption dan Sanctification ini merupakan konsep yang mendasar yang perlu dipahami dengan teguh karena berkaitan langsung dengan iman yang menyelamatkan. Konsep Adoption dan Sanctification yang teguh mampu menepis polemik atau keraguan tentang statusnya orang percaya di hadapan Allah. Penelitian ini menggunakan metode kualitatif dengan mendeskripsi konsep Adoption dan Sanctification melalui kajian keilmuan teologi sistematika.